Optimalisasi Proses Antrian di Gerai Es Krim KRM Dengan Pendekatan Simulasi ProModel - Utami, Ni Made Cyntia; Sitanggang, Bryan Estavan Imanuel; Anggita, I Gusti Agung Mas Putri; Pratiwiningsih, Windhi; Purnami, Ni Luh Dian (Politeknik ATI Padang, 2024)
KRM ice cream shop is a popular destination in Sanur, Bali. The intensity of customer visits on regular days is already quite crowded, even more so during the holiday season. Due to the location of Gerai KRM which is adjacent to the road sidewalk, it often causes congestion in the area. The long and less conducive queuing system is the main reason customers discourage coming. This research was conducted during peak hour, namely 11:00 to 13:00 which is lunch time. These data are then tested using the Stat::Fit feature to determine the type of data distribution. This type of data distribution will later be used to determine the length of the system process when tested in ProModel software, more precisely it will be included in the processing sequences section. The research results show that there is an entity of customers in waiting of 6.13% and blocked by 10.10% which is caused by a lack of capacity and service units in the system. Based on the problem, the proposed improvements given by the author are the addition of cashier units and also the queue capacity at the Ice Cream storefront service. The output of the proposed system simulation is a decrease in the percentage of blocked 1.32%. Then the percentage of full in the queue row which became 0% and the percentage of full in the ice cream storefront was reduced to 1.71%.